Sociological Analysis of Restorative Justice in Rehabilitative Law Enforcement for Drug Abuse Cases - Hermawan, Malsal Jajuli Haerudin; Wulansari, Catharina Dewi (Faculty of Law, Universitas Lampung, 2024)
The escalating trend in drug abuse, particularly among the youth, necessitates a unified approach from all law enforcement entities to address this shift in paradigm. It is essential to view drug addicts and victims of drug abuse not only as perpetrators but also as victims, warranting the incorporation of rehabilitation as an alternative form of punishment. The severity of narcotics crime in Indonesia poses a profound threat not only to individual health both physical and mental but also to societal well-being and national development, potentially compromising state security and sovereignty. This paper explores the enforcement of narcotics law in Indonesia as dictated by Law Number 35 of 2009 and examines the application of restorative justice, a concept often referred to in criminal law enforcement, which emphasizes recovery and atonement for the perpetrator or their family towards the victim, facilitating out-of-court reconciliatory efforts. By examining the legal sociological perspective, this research advocates for resolving narcotics-related criminal cases through means that prioritize restoration over retribution. It argues for a restorative justice approach, where the focus shifts from imprisonment to alternatives like medical and social rehabilitation, aiming for a resolution that restores harmony and agreement between involved parties, thereby aligning legal outcomes with societal values and needs.